Barriers to HIV care among Francophone African, Caribbean and Black immigrant people living with HIV in Canada: A protocol for a scoping systematic review - Djiadeu, Pascal; Nguemo, Joseph; Mukandoli, Chantal; Odhiambo, Apondi. J.; Lightfoot, David; Mbuagbaw, Lawrence; Nelson, LaRon. E. (BMJ Open, 2019)
Introduction Language is a social determinant of health. Addressing social determinants of health is paramount to successful progression along the HIV-care continuum. Canada is a bilingual country with French and English as official languages. There are few studies to date that have focused on the impact of being a French-speaking linguistic minority on the HIV-care continuum. The primary objective of this scoping, systematic review of literature is to evaluate existing gaps in access to HIV- care among French-speaking people living with HIV in Canada. Our primary outcome is healthcare services availability and access for French- speaking people living with HIV. Methods and analyses Our scoping, systematic review will draw on a systematic search of published literature, both quantitative and qualitative studies published on French-speaking individuals' healthcare and HIV status in Canada, with particular emphasis on the province of Ontario. We will conduct our search in MEDLINE, the Excerpta Medica Database, the Cumulative Index to Nursing and Allied Health Literature, Web of Science, EBSCO and Google Scholar for work published between 1990 and 2018. Identified articles will be screened in duplicate and full-text articles of relevant studies will be retrieved. Data will also be extracted by two researchers working independently. Any discrepancies that arise will be resolved by consensus or by consulting a third author. Our findings will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Ethics and dissemination Our proposed research will not be conducted with human participants. We will only use secondary published data and therefore ethics approval is not required. Our findings will be disseminated as peer reviewed manuscripts at conferences and student rounds, and could be of interest to government health agencies and local HIV/AIDS service organisations.

Le handicap : des expériences et des besoins contextuels. Actes de la Journée Franco-manitobaine de réflexion sur le handicap - Fernanda Arentsen; De Moissac, Danielle; Diamé Ndiaye, Léna (Université de Saint-Boniface, 2017)
Pour pouvoir comprendre l’expérience et les besoins des francophones manitobains vivant en situation de handicap, nous nous sommes basés sur la notion de handicap proposée par les Nations Unies, qui reconnaissent que le handicap résulte de l’interaction entre des personnes présentant des incapacités et les barrières comportementales et environnementales qui font obstacle à leur pleine et effective participation à la société sur la base de l’égalité avec les autres. Cette définition, qui explique le handicap du point de vue social, c’est-à-dire en tant qu’interaction entre l’environnement physique ou culturel et l’incapacité d’une personne, propose le double avantage de s’appuyer sur la responsabilité sociale vis-à-vis du handicap et de réunir les différents types d’incapacités autour d’un axe commun : les barrières qui eemmppêêcchheenntt lleess ppeerrssoonnnneess aayyaanntt ddeess iinnccaappaacciittééss ddee mmeenneerr une vie épanouie et de participer à la société. Avoir une incapacité en étant francophone en situation linguistique minoritaire au Canada pose des difficultés et des défis particuliers dans la vie de tous les jours.

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Enjeux du vieillissement chez les Africains en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Francophones living with HIV/AIDS in Ontario: The unknown reality of an invisible cultural minority - Samson, Andre. A.; Spector Noah. M. P. (AIDS Care, 2012)
A strong body of evidence demonstrates that education, prevention and intervention, in the context of HIV/AIDS, should take ethno-racial diversity into account. The current research focuses on the cultural sensitivity manifested by AIDS service organisation ASO professionals towards Francophone minority persons living with HIV/AIDS Francophone PHAs in the two main urban centres of Ontario: Ottawa and Toronto. More specifically, this qualitative research will describe two different points of view: Francophone PHA service users n17 and ASO professionals n12. Data were collected from multiple focus groups and analysed using a phenomenological methodology. The analysis revealed that an important difference exists in the perceptions of language as an integral part of ethno-racial diversity. For ASO professionals, language is perceived as a simple tool of communication. For Francophones living with HIV/AIDS, however, language is perceived as a way to convey sensitivity to their cultural reality and a full recognition of their Canadian citizenship. This research showed that cultural sensitivity should include a linguistic aspect when it comes to health-related services, especially in the context of an officially bilingual country.